Production Performance among The Restitution Farm Beneficiaries in Waterberg District, South Africa - Malose Moses Tjale; Marizvikuru Mwale; Beata M. Kilonzo (AGRARIS: Journal of Agribusiness and Rural Development Research, 2022)
Farmland was regarded as the most important asset used to enhance agricultural productivity in developing countries to improve the livelihoods of restitution farm beneficiaries. Most, unfortunately, recent reports show decreased agricultural productivity in most developing countries. In South Africa, the Land restitution program was introduced to restore land to people dispossessed by apartheid government after 1913. However, production in the restitution farms has declined. This study aimed to address the non-performance of the restitution farms in Waterberg District and evaluate their production performance. A questionnaire was administered to gather quantitative data on the farms’ production and the benefits accrued from the farms. Data was captured using Geographic Information System (GIS), and then a remote sensing analysis method was used to map restitution farms to illustrate farms performance. Statistical Package for the Social Scientists (SPSS) version 25 was used to compute statistics on-farm production. About 83% of beneficiaries have not benefitted from the 32 farms, while 61.6% did not have markets, and 64% reported a lack of farms income. Generally, lack of farm production impeded beneficiaries from receiving benefits and employment. The study recommended that private organizations and sector departments work together to assist beneficiaries with capacity building, marketing of farm produce, and funds to improve production.